2012
DOI: 10.1016/j.jep.2012.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Potential behavioral and pro-oxidant effects of Petiveria alliacea L. extract in adult rats

Abstract: The Petiveria alliacea extract exerted motor stimulatory and anxiolytic effects in the OF test, antidepressant effects in the FS test, and elicited memory improvement in ETM. Furthermore, the Petiveria alliacea extract also exerted pro-oxidant effects in vitro and in vivo, inhibiting the antioxidant status and increasing MetHb levels in human plasma, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
1
17
0
2
Order By: Relevance
“…Moreover, lesions can lead to cell inactivation, as well as mutagenic potential (Friedberg et al, 2006), justifying the need for further such studies in other experimental models, such as bacteria and eukaryotic cells. In addition, some studies suggest that various extracts or compounds of this species exhibit antioxidant or pro-oxidant activity (Carlini, 2003;Andrade et al, 2012). In this work, the antigenotoxic effect was influenced by plant origin, suggesting, in turn, the influence of some genetic variation.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Moreover, lesions can lead to cell inactivation, as well as mutagenic potential (Friedberg et al, 2006), justifying the need for further such studies in other experimental models, such as bacteria and eukaryotic cells. In addition, some studies suggest that various extracts or compounds of this species exhibit antioxidant or pro-oxidant activity (Carlini, 2003;Andrade et al, 2012). In this work, the antigenotoxic effect was influenced by plant origin, suggesting, in turn, the influence of some genetic variation.…”
Section: Discussionmentioning
confidence: 54%
“…Some studies have reported on the pro-oxidant effects of this species in different experimental models (Salim, 2011;Andrade et al, 2012). Using a sea urchin model, a moderate genotoxic activity, based on cytogenetic changes, was reported (Hoyos et al, 1992), but to our knowledge, this is the first study on the effect of extracts of P. alliacea on the DNA molecule.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Petiveria alliacea is an important Amazonian herb with (Andrade et al, 2012;Silva et al, 2015). Although previous studies have demonstrated that P. alliacea induces genotoxic hazards in low concentrations, there is a lack of information about the effects of high concentrations of ethanolic preparations in both in vitro and in vivo models.…”
Section: Discussionmentioning
confidence: 99%
“…The hydroalcoholic extract was choosen because previous studies of our group have demonstrated its potential effects on central nervous system when comparing with traditionally preparations (Andrade et al, 2012;Silva et al, 2015). Crude EHPa was prepared through the maceration method.…”
Section: Extract Preparationmentioning
confidence: 99%